(untitled) (Estudios Sociales, 2021)
How are culture and nature represented in Tierra del Fuego National Park? The interest in addressing this question is to reflect on protected areas and, from there, analyze State policies of intervention in environmental conservation issues. With this objective we will study the Maiá-Kú interpretive center and the brochures offered in this national park. We understand that the culture-nature dichotomy is a particular type of interpretation of environmental conservation